Estrutura simplética para teorias de spin alto pela descrição de twistors - Flores, Henrique dos Santos [UNESP] (2014)
We write a symplectic form on higher spin theories using twistor description. Our approach follows from Penrose’s equations, and our results seem to suggest an action di?erent from Fronsdal theory. Di?erences between the two approaches also appear, although they are, essentially, equivalent